2017
DOI: 10.2136/vzj2016.08.0073
|View full text |Cite
|
Sign up to set email alerts
|

Study of Activation Energy in Soil through Elastic Wave Velocity and Electrical Resistivity

Abstract: Core Ideas• The Arrhenius equation was applied to predict geophysical properties. • Elastic and electromagnetic waves were selected. • The activation energy exhibited a nonlinear curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In addition, the elastic wave velocity seems to be a good indicator of soil stiffness, and the detailed analyses associated with activation energy analyzed in the context of V p and V s are discussed in the sections below. The results revealed that the water-to-ice phase transformation resulted in a sharp increase in E a near the freezing temperature and a decrease in its bandwidth with a decrease in ∆T, which is consistent with the findings of Lee et al (2017). Particularly, the homogeneously mixed and evaporation-driven specimens exhibited higher E a , whereas the horizontally layered specimen exhibited the lowest E a .…”
Section: Wave Velocitysupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the elastic wave velocity seems to be a good indicator of soil stiffness, and the detailed analyses associated with activation energy analyzed in the context of V p and V s are discussed in the sections below. The results revealed that the water-to-ice phase transformation resulted in a sharp increase in E a near the freezing temperature and a decrease in its bandwidth with a decrease in ∆T, which is consistent with the findings of Lee et al (2017). Particularly, the homogeneously mixed and evaporation-driven specimens exhibited higher E a , whereas the horizontally layered specimen exhibited the lowest E a .…”
Section: Wave Velocitysupporting
confidence: 87%
“…In this study, the effects of the water distribution patterns on the activation energy of unsaturated soils subjected to phase transformations were investigated using elastic wave velocity. This study utilized the physical concepts and fundamental observations reported by Lee et al (2017). We then extend their works to the activation energy of partiallysaturated soils with different water distribution patterns subjected to a freeze-thaw cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have tried to study pore structure with experimental techniques that consider component analysis, pore size distribution and the saturated condition. Meanwhile, the geophysical method is an alternative method to determine the contact mechanism in porous materials at a small strain range [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Equation (2) is often used in the field of geotechnical and geological engineering to derive porosity as a design parameter [ 17 , 18 ]. In addition, studies to understand particle properties were performed by linking the contact characteristics and cementation effects of soil materials since α and m values were related to particle shape [ 19 , 20 ].…”
Section: Background Theorymentioning
confidence: 99%